Kinetic properties of glutathione-S-transferase in prostate gland biopsies of patients with benign prostatic hyperplasia and chronic prostatitis - M. E. Kushynska; O. K. Onufrovych; D. Z. Vorobets; A. S. Besedina; G. V. Galyk; O. I. Pershyn; R. V. Fafula; Z. D. Vorobets (Regulatory Mechanisms in Biosystems, 2025)
The molecular and stromal mechanisms associated with the pathogenesis of prostate hyperplasia as a metabolic disorder are not yet fully understood, but it is believed that the etiology of hyperplasia is influenced by a number of factors, including aging, hormonal changes, metabolic syndrome, dietary factors, inflammation, oxidative stress, and, more recently, suppression of apo p tosis in prostate tissue. A number of studies emphasize the disruption of pro/antioxidant status in the development of prostate hyperplasia. The aim of the research is to study the activity and kinetic characteristics of glutathione-S-transferase (GsT) in pro s tate biopsies from patients with benign hyperplasia and hyperplasia with chronic prostatitis. The prostate tissue (biopsies) from two groups of patients were used. Group 1 consisted of patients with benign prostatic hyperplasia (n = 14); group 2 consisted of patients with benign prostatic hyperplasia and chronic prostatitis (n = 14). It was shown that GsT activity in the soluble fraction of prostate biopsies from patients with benign hyperplasia with chronic prostatitis was 1.60 times higher than in patients without chronic prostatitis. It was found that the kinetics of the GsT reaction is consistent with the patterns of a zero-order reaction in the range of 0–3 min: in this time interval, the dependence graph of the product formation on the incubation period was practically linear. It was shown that the value of V 0 in patients with prostatic hyperplasia with chronic prostatitis wa s almost twice as high as that in patients without chronic prostatitis. Over the entire range of GSH concentrations, enzyme activity in samples from patients with inflammation was higher than in patients without chronic prostatitis. Similar changes were also observed with an increase in the concentration of 1-chloro-2,4-dinitrobenzene in the incubation medium at a constant GSH concentrations. Calculation of the kinetic parameters of GsT activity shows that the maximum reaction rate of accumulation of the optically active dinitrobenzene conjugate, determined by GSH, was 1.44 times higher in patients with chronic prostatitis compared to the first group. The affinity constant for GSH in this group of patients was 2.28 times higher compared to patients without chronic prostatitis. When interpre t ing the obtained kinetic parameters determined by GSH, it is shown that GsT activity in patients with benign prostatic hyperplasia without chronic prostatitis is reduced both due to a decrease in the enzyme reaction rate (V max decreases) and due to a increase in the enzyme's affinity for GSH (KGSH decreases).